Cartels and Casinos: First Nations’ Gaming in Canada - Flanagan, Tom (Fraser Institute, 2020)
In 1985, Parliament amended the Criminal Code to give the provinces jurisdiction over gambling. The provinces have used their new jurisdiction to create cartels for their own profit, in which they are either the owners of licensed casinos or take a large share of the profit. First Nations challenged the provinces in court but lost. Hence, they have had to fit into the cartel system and take leftovers—with a few exceptions, casinos located far from the main action. Only Alberta has let them into lucrative metropolitan markets, with one casino each in Edmonton and Calgary. Saskatchewan and Manitoba have recently licensed First Nation casinos not too far from Saskatoon and Winnipeg. In Ontario, Casino Rama is in a popular resort location, and the Membertou VLT parlours are situated within the small city of Sydney, Nova Scotia.Obviously a lot of money moves around in casinos, but does it benefit the host First Nations? The answer is an emphatic “Yes” for the half-dozen casinos located in or near cities and destination resorts. In all these cases, the opening of a casino was an inflection point in the time series of their Community Well-Being (CWB) index scores. (CWB is an aggregate of income, employment, education, and housing data collected by Statistics Canada.) Their scores rose more rapidly than their previous rate of progress because large profits from the casino can be used to provide better housing and other social services for First Nation members. Money from the casinos can also be leveraged for large-scale business and real-estate development, as is now happening in Edmonton and Calgary.Elsewhere, the answer is only a qualified “Yes”. The casinos in rural locations are generally profitable and honestly run, and they do generate useful amounts of cash and jobs for the host First Nations. However, in most cases hosting a casino has no discernible effect on the Community Well-Being of the hosts. The CWB scores of less favourably located First Nation casinos have not risen more rapidly than the general rate of ...